Using cognitive artefacts to aid decision-making in railway signalling operations - Charles, Rebecca (2014)
This thesis presents work undertaken in conjunction with Network Rail in the area of planning and re-planning in railway environments. It aimed to study a real world signalling environment to understand the strategies signallers use when re-planning and how decision tools can be designed and integrated into existing signalling environments to support proactive planning.